In vitro biological evaluation and in silico insights into the antiviral activity of standardized olive leaves extract against SARS-CoV-2 - Majrashi, Taghreed A.; El Hassab, Mahmoud A.; Mahmoud, Sara H.; Mostafa, Ahmed; Wahsh, Engy A.; Elkaeed, Eslam B.; Hassan, Fatma E.; Eldehna, Wagdy M.; Abdelgawad, Shimaa M. (PLOS ONE, 2024)
There is still a great global need for efficient treatments for the management of SARS-CoV-2 illness notwithstanding the availability and efficacy of COVID-19 vaccinations. Olive leaf is an herbal remedy with a potential antiviral activity that could improve the recovery of COVID-19 patients. In this work, the olive leaves major metabolites were screened in silico for their activity against SARS-CoV-2 by molecular docking on several viral targets such as methyl transferase, helicase, Plpro, Mpro, and RdRp. The results of in silico docking study showed that olive leaves phytoconstituents exhibited strong potential antiviral activity against SARS-CoV-2 selected targets. Verbacoside demonstrated a strong inhibition against methyl transferase, helicase, Plpro, Mpro, and RdRp (docking scores = -17.2, -20, -18.2, -19.8, and -21.7 kcal/mol.) respectively. Oleuropein inhibited 5rmm, Mpro, and RdRp (docking scores = -15, -16.6 and -18.6 kcal/mol., respectively) respectively. Apigenin-7-O-glucoside exhibited activity against methyl transferase and RdRp (docking score = -16.1 and -19.4 kcal/mol., respectively) while Luteolin-7-O-glucoside inhibited Plpro and RdRp (docking score = -15.2 and -20 kcal/mol., respectively). The in vitro antiviral assay was carried out on standardized olive leaf extract (SOLE) containing 20% oleuropein and IC50 was calculated. The results revealed that 20% SOLE demonstrated a moderate antiviral activity against SARS-CoV-2 with IC50 of 118.3 μg /mL. Accordingly, olive leaf could be a potential herbal therapy against SARS-CoV-2 but more in vivo and clinical investigations are recommended.